Thioredoxin deficiency exacerbates vascular dysfunction during diet‐induced obesity in small mesenteric artery in mice. (30th December 2020) - Dunn, Shannon; Hilgers, Robert H.; Das, Kumuda C.
Abstract: Objective: Thioredoxin (Trx) is a small cellular redox protein with established antioxidant and disulfide reductase properties. We hypothesized that Trx deficiency in mice would cause increased oxidative stress with consequent redox imbalance that would exacerbate obesity‐induced vascular dysfunction. Methods: Non‐transgenic (NT, C57BL/6) and dominant‐negative Trx (dnTrx‐Tg, low levels of redox‐active protein) mice were either fed a normal diet (NC) or high fat diet plus sucrose (HFS) diet for 4 months (3‐month HFD+ 1‐month HFS). Weight gain, glucose tolerance test (GTT), insulin tolerance test (ITT), and other metabolic parameters were performed following NC or HFS diet. Arterial structural remodeling and functional parameters were assessed by myography. Results: Our study found that dnTrx mice with lower levels of active Trx exacerbated myogenic tone, inward arterial remodeling, arterial stiffening, phenylephrine‐induced contraction, and endothelial dysfunction of MA. Additionally, FeTMPyP, a peroxynitrite decomposition catalyst, acutely decreased myogenic tone and contraction and normalized endothelial function in MA from dnTrx‐Tg mice on HFS via increasing nitric oxide (NO)‐mediated relaxation. Conclusions: Our results indicate that deficiency of active Trx exacerbates MA contractile and relaxing properties during diet‐induced obesity demonstrating that loss of redox balance in obesity is a key mechanism of vascular endothelial dysfunction.